Nudging cooperation in public goods provision - Kai Barron; Tuomas Nurminen (Journal of Behavioral and Experimental Economics, 2020)
This paper experimentally studies two simple interventions that an authority figure might employ to promote cooperation in a public goods game when accurate feedback about contributions is not available. The first intervention aims to nudge participants to higher contribution levels by labeling contributions above a particular threshold as being `good'. Such a `norm-nudge' is intended to provide subjects with a clear, valenced focal point upon which they can coordinate. The second intervention aims to exploit lying aversion to induce higher contributions by requiring subjects to announce how much they contributed. We find that the nudge leads to a striking increase in the cooperation rate. By contrast, the ex post announcement mechanism does not have a significant effect on the cooperation rate. We present suggestive evidence that the nudge we use provides subjects with a focal point, helping conditional cooperators to coordinate their contributions.
Older version: http://hdl.handle.net/10419/193680
Keywords: C91; C72; H41; Z13; 330; cooperation; nudge; focal point; public good; lying; experiment